حال المنازعات الناشئة عن التقصير في عقد الإيجار: دراسة في شركة BOWRIZ لإجارة السيارات بماجيلانج في منظور الشريعة الإسلامية - Lahuri , Setiawan; Putra , Okky Mahdi Indrawan; Zuhroh , Ainun Amalia (LPPPM STAI Darul Hikmah Bangkalan, 2022)
Along with the development of the times, several people or companies that are engaged in car rental have emerged because of the importance of transportation, especially cars and very expensive car prices. From this rental, a lease agreement or ijarah emerg es. For rental owners and tenants, they want to get mutually beneficial reciprocity, but in reality, on the ground, there is a situation where achievement is not achieved or is said to be